Advances in Potential Cerebrospinal Fluid Biomarkers for Autoimmune Encephalitis: A Review - Zhang, Shuyu; Mao, Chengyuan; Li, Xinwei; Miao, Wang; Teng, Junfang (Frontiers in Neurology, 2022)
Autoimmune encephalitis (AE) is a severe inflammatory disease of the brain. Patients with AE demonstrate amnesia, seizures and psychosis. Recent studies have identified numerous associated autoantibodies (e.g. against NMDA receptors (NMDARs), LGI1, etc.) involved in the pathogenesis of AE, the level of diagnosis and treatment are thus improved dramatically. However, there are drawbacks of clinical diagnosis and treatment based solely on antibodies levels, the application of additional biomarkers is urgently needed. Considering the important role of immune mechanisms in AE development, we summarize the relevant research progress in identifying cerebrospinal fluid (CSF) biomarkers with a focus on cytokines/chemokines, demyelination, and nerve damage.